Herbicides, Physiology of Action, and Safety 2015
DOI: 10.5772/60858
|View full text |Cite
|
Sign up to set email alerts
|

Triazine Herbicides in the Environment

Abstract: This chapter is a review of literature concerning the fate of chloro-s-triazine herbicides, particularly atrazine, in the environment. It addresses the distribution of such herbicides and their metabolites in the soil and in water bodies, including the conditions that affect their transport mechanisms. The biodegradation pathways regarding the microbial degradation are presented as well as modification mechanisms of the compounds in plants capable of tolerating their action. Studies on the influence of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…In certain studies, human exposure to high doses of atrazine can cause loss of body weight. Nevertheless, several epidemiological studies done with workers usually exposed to triazine indicate that these compounds show no potentials of been carcinogenic to the workers [20]. Furthermore, via analyses of different studies, it was observed that, though the chloro-s-triazine interferes in the endocrine responses of different species of mammals, their impending impact on humans seems to be primarily related to reproduction and development and not with human carcinogenesis [21].…”
Section: Effect Of Chemical Pesticides On Safety Of Food: Research St...mentioning
confidence: 99%
“…In certain studies, human exposure to high doses of atrazine can cause loss of body weight. Nevertheless, several epidemiological studies done with workers usually exposed to triazine indicate that these compounds show no potentials of been carcinogenic to the workers [20]. Furthermore, via analyses of different studies, it was observed that, though the chloro-s-triazine interferes in the endocrine responses of different species of mammals, their impending impact on humans seems to be primarily related to reproduction and development and not with human carcinogenesis [21].…”
Section: Effect Of Chemical Pesticides On Safety Of Food: Research St...mentioning
confidence: 99%
“…The major commercial symmetrical triazines are further divided into chloro-s-triazines (atrazine, propazine, terbutylazine), thiomethyl-s-triazines (ametryn, terbutryn), and methoxy-s-triazine (prometon) (58). Recent years saw a growing concern about the toxicity and environmental persistence and mobility of triazines and their metabolites (59). Atrazine has been used extensively, mainly due to its low cost and ease of application and is the most common contaminant of groundwater and surface water.…”
Section: Triazine Herbicidesmentioning
confidence: 99%
“…Other widely used 1,3,5-triazines are, e.g., cyanuric chloride (2,4,6-trichloro-1,3,5-triazine) and 6-alkyl/aryl-1,3,5-triazine-2,4-diamines. Triazine-based agents such as atrazine, ametryn, prometryn, cyanazine, propazine, simazine, terbuthylazine and terbutryn are highly effective herbicides [3], unfortunately also with strong adverse impacts on humans and the environment [4][5][6][7][8][9]. On the other hand, 1,3,5-triazines represent a remarkable platform for the design of potential drugs, especially with anti-infective (antiviral, antibacterial, antimycobacterial, antifungal, antiprotozoal, anthelmintic) and anticancer effects, but also with anti-inflammatory, antidiabetic, antioxidant, antiulcer, anticonvulsant and cardioprotective activities, depending on the specific substitution of the 1,3,5-triazine scaffold [1,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%